Latanoprost and Herpetic Keratitis - Muhammad Moin, Imran Attaulla, Mazhar Zaman Soomro (Pakistan Journal of Ophthalmology, 2011)
Herpetic Simplex is a common cause of infection of the cornea. Primary open angle Glaucoma (POAG) is the most common cause of irreversible blindness in the world. Prostaglandin analogues are commonly prescribed as the first line therapy for POAG. This is a report of a patient with recurrence of herpetic keratitis, who was on latanoprost for two months. Clinicians should be alert to Latanoprost as a cause of recurrence of herpetic keratitis.